Reticuloendotheliosis Virus Inhibits the Immune Response Acting on Lymphocytes from Peripheral Blood of Chicken - Bi, Yulin; Xu, Lu; Qiu, Lingling; Wang, Shasha; Liu, Xiangping; Zhang, Yani; Chen, Yang; Zhang, Yang; Xu, Qi; Chang, Guobin; Chen, Guohong (Frontiers in Physiology, 2018)
Chicken reticuloendotheliosis virus (REV) causes the atrophy of immune organs and immuno-suppression. The pathogenic mechanisms of REV are poorly understood. The aim of this study was to use RNA sequencing to analyse the effect of REV on immunity and cell proliferation in chicken lymphocytes from peripheral blood in vitro. Overall, 2977 differentially expressed genes (DEGs) were examined from cells between infected with REV or no; 56 DEGs related to cell proliferation and 130 DEGs related to immunity were identified. MTT, Q-PCR and FCM indicated that REV reduced the number of lymphocytes by inhibiting the transition of S/G1 phase through FOXO and p53 pathways. Similarly, REV infection would destroy the immune defense of lymphocytes through MAPK-AP1 via Toll-like receptor-, NOD-like receptor- and salmonella infection pathways to reduce the secretion of IL8 and IL18. In addition, the reduction of lymphocytes also might be responsible for the lower levels of IL8 and IL18, and the rescue of lymphocytes would been activated still through FOXO and p53 pathways. Moreover, the immune response for REV in lymphocytes would activate by up-regulating the expression of NOD1, MYD88 and AP1 through Toll-like receptor-/NOD-like receptor/salmonella-MAPK-AP1 pathways. These results indicate that REV could affect lymphocytes from peripheral blood by inhibit the cell proliferation and the immune system. It also was revealed that NOD1, MYD88 and AP1 were the key genes to activate the immune response through Toll-like receptor-/NOD-like receptor/salmonella-MAPK-AP1 pathways. These findings establish the groundwork and provide new clues for deciphering the molecular mechanism underlying REV infection in chickens.